Optical characterization of lorentz force based CMOS-MEMS magnetic field sensor - Dennis, J.O. (MDPI AG, 2015)
Magnetic field sensors are becoming an essential part of everyday life due to the improvements in their sensitivities and resolutions, while at the same time they have become compact, smaller in size and economical. In the work presented herein a Lorentz force based CMOS-MEMS magnetic field sensor is designed, fabricated and optically characterized. The sensor is fabricated by using CMOS thin layers and dry post micromachining is used to release the device structure and finally the sensor chip is packaged in DIP. The sensor consists of a shuttle which is designed to resonate in the lateral direction (first mode of resonance). In the presence of an external magnetic field, the Lorentz force actuates the shuttle in the lateral direction and the amplitude of resonance is measured using an optical method. The differential change in the amplitude of the resonating shuttle shows the strength of the external magnetic field. The resonance frequency of the shuttle is determined to be 8164 Hz experimentally and from the resonance curve, the quality factor and damping ratio are obtained. In an open environment, the quality factor and damping ratio are found to be 51.34 and 0.00973 respectively. The sensitivity of the sensor is determined in static mode to be 0.034 Î¼m/mT when a current of 10 mA passes through the shuttle, while it is found to be higher at resonance with a value of 1.35 Î¼m/mT at 8 mA current. Finally, the resolution of the sensor is found to be 370.37 Î¼T. Â© 2015, by the authors, licensee MDPI, Basel, Switzerland.